PENGARUH FREE CASH FLOW DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Br Meliala, Keren Tireya; Damanik, Dennys Paulus Parlindungan; Sembiring, Yosephine Natalitha; Ginting, Mitha Christina (Journal Accounting International Mount Hope, 2024)
This study aims to determine the effect of free cash flow and managerial ownership on debt policy in manufacturing companies listed on the Indonesian stock exchange. This study uses secondary data which can be accessed through the Indonesia Stock Exchange website (www.idx.co.id). The population of this study consisted of 23 manufacturing companies in the textile and garment sector listed on the IDX for the 2017-2021 period and the sampling method was carried out using purposive sampling method. With this method, a sample of 10 companies was obtained with a 5-year observation method. So that the number of observations for this study is 50 observations. To analyze the effect of free cash flow and managerial ownership on debt policy, multiple linear analysis is used with the classic assumption test. The results of this study indicate that free cash flow partially has no significant effect on debt policy and managerial ownership partially has a significant effect on debt policy.